Explorations of the Life-World
VIII, 288 p.
Keywords: This anthology originated from three conferences, which were held at Waseda University, Tokyo, Japan, on March 26-28, 1999, at the Univ- sity of Konstanz, Germany, on May 26-29, 1999 and a session at the SPHS annual meeting at the University of Oregon, USA, on October 5-7, 1999. With one exception the contributions to this volume are revised versions of papers read at these meetings. Each of these conferences took place in order to celebrate the centennial of the birthday of Alfred Schutz, who was born April 13, 1899, and died May 20, 1959. First of all we would like to thank Evelyn Schutz-Lang, the daughter of Alfred and Ilse Schutz, for her continuing support and encouragement. Moreover, Evelyn Schutz-Lang as well as Claudia Schutz, the gr- daughter of Alfred and Ilse Schutz, and the daughter of his son George, gave us the honor of visiting the Konstanz conference in 1999. Evelyn also came to the Oregon conference and sent her personal greetings to those attending the Tokyo conference. We would like to thank Waseda University, the Waseda Sociological Association, the Waseda University International Conference Center, and the Center for Research in Human Sciences in Japan for their generous financial support, as well as the German Research Council (Deutsche Forschungsgemeinschaft), the University of Konstanz, the Alfred Schutz Memorial Archives in Konstanz, and the Sparkasse Konstanz for their considerable financial assistance in making the conferences possible.